Refurbishing used GPS transmitters improves performance for subsequent deployments on greater sage‐grouse - Melissa S. Chelak; Michel T. Kohl; Justin R. Small; Kurt T. Smith; Aaron C. Pratt; Jeffrey L. Beck; Codi R. Backen; M. Brandon Flack; Hailey P. Wayment; Jason A. Wood; Ryan Howell; Trevon D. Strange; et al. (Wildlife Society Bulletin)
Abstract Global Positioning Systems (GPS) radio transmitters are increasingly used across taxa to monitor animal populations. However, GPS transmitters can be susceptible to malfunctions that may result in location errors or data loss causing potential inferential bias that can have important implications for monitored species. Research using GPS transmitters on greater sage‐grouse (Centrocercus urophasianus; sage‐grouse) has increased, but few sage‐grouse studies have evaluated GPS performance. Because sage‐grouse management has been subject to intense legal and political scrutiny with consequential economic implications, reliable data acquisition is central to informed decision‐making for the species. We evaluated differences in the performance of 2 commonly used solar‐powered GPS transmitters (Microwave Telemetry, Inc. [MTI], Columbia, MD, USA and GeoTrak, Inc., Apex, NC, USA) deployed on sage‐grouse throughout Wyoming from 2011 to 2017 and Utah from 2013 to 2019. Our investigation of GPS performance included daily fix inefficiency, the number of 1‐day fix gaps, and transmitter loss rate. We also evaluated transmitter functionality during the nesting period including daily nesting fix inefficiency, fix error distance mean and standard deviation (i.e., accuracy and precision), and mean fix error direction. New and refurbished MTI transmitters outperformed GeoTrak transmitters in daily fix inefficiency and day gaps during most seasons. Cumulatively redeployed MTI transmitters did not perform differently than GeoTrak transmitters. Transmitter loss, daily nesting fix inefficiency, and nest fix precision did not vary significantly between the 2 transmitters. GeoTrak performed better than MTI for nest fix accuracy across all latitudes (40–45° N). The mean error direction to the nest location ranged between 105° and 135° for GeoTrak and between 135° and 155° for MTI. We recommend refurbishing transmitters following deployment to retain higher fix efficiency than cumulatively redeploying transmitters.